2011
DOI: 10.14310/horm.2002.1288
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: Its emerging role in oncology

Abstract: Metformin is considered, in conjunction with lifestyle modification, as a first-line treatment modality for type 2 diabetes mellitus (DM). recently, several clinical studies have reported reduced incidence of neoplastic diseases in DM type 2 patients treated with metformin, as compared to diet or other antidiabetic agents. Moreover, in vitro studies have disclosed significant antiproliferative and proapoptotic effects of metformin on different types of cancer. Metformin acts by activating AMP-activated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 86 publications
(87 reference statements)
1
26
0
Order By: Relevance
“…AICAR is converted to its metabolite ZMP (AICAR monophosphate) [29], which mimics the effects of AMP on AMPK kinase while the cellular levels of AMP, ADP and ATP remain unaffected [30,31]. Metformin can activate AMPK via its upstream kinase LKB1, mitochondrial respiratory chain block and reduction of the intracellular ATP concentration [32,33], or inhibition of AMP-deaminase [34], which leads to increased levels of AMP and reduced ATP. This lowering of intracellular ATP might impede insulin secretion by keeping K ATP channels in the open state, thereby overcoming a possible inhibitory action of AMPK on these channels under metformin [14].…”
Section: Discussionmentioning
confidence: 99%
“…AICAR is converted to its metabolite ZMP (AICAR monophosphate) [29], which mimics the effects of AMP on AMPK kinase while the cellular levels of AMP, ADP and ATP remain unaffected [30,31]. Metformin can activate AMPK via its upstream kinase LKB1, mitochondrial respiratory chain block and reduction of the intracellular ATP concentration [32,33], or inhibition of AMP-deaminase [34], which leads to increased levels of AMP and reduced ATP. This lowering of intracellular ATP might impede insulin secretion by keeping K ATP channels in the open state, thereby overcoming a possible inhibitory action of AMPK on these channels under metformin [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that metformin administration significantly reduces the incidence and mortality rates of various types of cancer, including gastric cancer (4)(5)(6). According to the findings reported by a previous study, patients who were treated with metformin hada lower incidence of gastric cancer, compared with those who did not receive metformin treatment (7).…”
Section: Introductionmentioning
confidence: 92%
“…This causes reduction in lipogenesis and synthesis of the acetyl-CoA carboxylase product malonyl-CoA resulting in increased fatty acid oxidation. Moreover, AMPK activation may result in p53 activation, which is a tumor suppressor that is often mutated in other type of cancer [19,20] . There have been several in vitro and in vivo studies on papillary, medullary, and anaplastic thyroid cancer cell lines evaluating the effects of metformin on the suppression of clonal growth, self-renewal, and proliferation of cancer stem cells [9,10,21,22] .…”
Section: Metformin and Thyroid Cancermentioning
confidence: 99%